Core Job Characteristic and Uncertainty Avoidance: Into the Black Box of Transformational Leadership Effect on Creativity. (26th July 2018) - Wang, Peng
Abstract: Drawing upon the job characteristic model and the "management of meaning" perspective, this study examines the process and conditions through which transformational leadership fosters employee creativity. Our results reveal that the effect of transformational leadership on creativity is mediated by employees' perceptions of core job characteristics (variety, identity, significance, autonomy, feedback). This mediation effect is further moderated by employees' uncertainty avoidance orientation. Specifically, transformational leaders foster creativity through followers' perceptions of core job characteristics only among employees low on uncertainty avoidance. The association between enhanced job characteristics and creativity is more positive for employees with low uncertainty avoidance orientation than those with high uncertainty avoidance orientation. Implications and future research directions are discussed.